Multiphoton Microscopy in the Biomedical Sciences XIX 2019
DOI: 10.1117/12.2508373
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field multiphoton imaging with TRAFIX

Abstract: Optical approaches have broadened their impact in recent years with innovations in both wide-field and superresolution imaging, which now underpin biological and medical sciences. Whilst these advances have been remarkable, to date, the ongoing challenge in optical imaging is to penetrate deeper. TRAFIX is an innovative approach that combines temporal focusing illumination with single-pixel detection to obtain wide-field multiphoton images of fluorescent microscopic samples deep through scattering media withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, TF has come to the forefront with the realisation that spectrally dispersed light preserves spatial fidelity throughout scattering media due to the temporal pulse compression being supported only by the inphase, minimally scattered photons [10][11][12][13]. Wide-field TF MPM has been demonstrated as a novel option for correction-free imaging at a depth of up to seven scattering mean-free-path lengths with two-photon [10] excitation and may go further using three-photon [14] excitation modes. This advance (termed TRAFIX) was enabled with single-pixel detection, wherein structured patterns are sequentially projected onto the sample plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TF has come to the forefront with the realisation that spectrally dispersed light preserves spatial fidelity throughout scattering media due to the temporal pulse compression being supported only by the inphase, minimally scattered photons [10][11][12][13]. Wide-field TF MPM has been demonstrated as a novel option for correction-free imaging at a depth of up to seven scattering mean-free-path lengths with two-photon [10] excitation and may go further using three-photon [14] excitation modes. This advance (termed TRAFIX) was enabled with single-pixel detection, wherein structured patterns are sequentially projected onto the sample plane.…”
mentioning
confidence: 99%
“…In this paper, we have demonstrated that the random Morlet basis, based on Gabor's minimisation of the uncertainty criteria, presents an elegant and optimal solution to compressive imaging in microscopy. Very recently, we have seen a flurry of demonstrations combining wide-field temporal focusing with single-pixel detection to achieve correction-free multiphoton imaging at im-proved depths [10][11][12]14]. Fortuitously, this geometry lends itself to CS, with prospects to increase acquisition speed and minimise photobleaching, which in itself TRAFIX minimises compared to standard point-scanning approaches.…”
mentioning
confidence: 99%